RELATIONSHIP BETWEEN SEED VIABILITY LOSS AND SEED BANK REDUCTION OF OROBANCHE AEGYPTIACA PERS. USING NON-HOST CROPS - Acharya, Bipana Devi (Ecoprint: An International Journal of Ecology, 2014)
Orobanche spp. are serious and difficult weed to control to many economically important plants. Theseed bank of this noxious weed in soil can be reduced by using trap crop. But all the seed bankreduction is not due to trap crop only; some reduction is also contributed by edaphic and/orpathogenic factors. So in the present study, the relationship between reduction in Orobanche seedbank in soil and loss of seed viability due to trap crop has been investigated in pots and naturalinfested fields at Vedabari (Field A) and Beldia (Field B). Results of viability loss and seed bankreduction indicated that nearly 11% to 25% of the reduction of seed density of Orobanche in soil iscontributed by seed viability loss due to trap crops. On combining data of all three experiments, itwas found that the loss of seed viability in Orobanche due to combined effects of treatments with testcrops was nearly 24%. When the value obtained from viability loss and seed bank reduction iscompared with the value obtained in control treatment, it is found that the contribution of edaphicfactors for seed bank reduction is about 76% and that of tested trap crops is about 24%, respectively. DOI: http://dx.doi.org/10.3126/eco.v20i0.11471 ECOPRINT An International Journal of Ecology Vol. 20, 2013 page: 97-106